Islamic Values behind The Ritual of A Cow Head Burial in Grebeg Suro - Yurisa, Penny Respati; Fu'aturosida, Rika; Agung, Yusuf Ratu; Muhayani, Ulfah (el Harakah: Jurnal Budaya Islam, 2021)
This paper aims to uncover the Islamic values behind the ritual of a cow head burial held by people in Bamboo Forest, Sumbermujur, Candipuro, Lumajang. It is one of the rituals of a popular Javanese culture called Grebek Suro, conducted in the first month of the Javanese calendar. It finds that the Islamic value of the ritual is salam or safety. The cow head burial is intended to bring about safety (slamet) towards society in the upcoming year. This research is expected to contribute in calling people for preserving local culture and Islamic values within the rituals. It is limited to the exploration of the Islamic values within the ritual of a cow head burial in Grebeg Suro ceremony. Further researches are expected to study the other rituals, such as Gunungan, Tumpengan, Japa Mantra, Larungan, and the dancing ritual. Tulisan ini bertujuan untuk mengungkap nilai Islam di balik ritual penanaman kepala sapi yang dilakukan oleh masyarakat di Hutan Bambu, Sumbermujur, Candipuro, Lumajang. Ini adalah salah satu ritual budaya Jawa terkenal, Grebek Suro, yang dilakukan pada bulan pertama penanggalan Jawa. Studi ini menemukain bahwa nilai Islam dari ritual tersebut adalah salam atau keselamatan. Penguburan kepala sapi dimaksudkan untuk membawa keselamatan (slamet) bagi masyarakat di tahun mendatang. Penelitian ini diharapkan dapat berkontribusi dalam mengajak masyarakat untuk melestarikan budaya lokal dan nilai-nilai Islam dalam ritualnya. Penelitian ini terbatas pada penggalian nilai-nilai Islam dalam ritual penguburan kepala sapi di upacara Grebeg Suro. Penelitian selanjutnya diharapkan menganalisis ritual-ritual lainnya, seperti Gunungan, Tumpengan, Japa Mantra, Larungan, dan ritual menari.